RQL 370 - Kajian Ukur Bahan Peranan Insurans Terhadap Pengurusan Risiko Projek Binaan Oleh Kontraktor - Fadila, Rayhan (Universiti Sains Malaysia, 2007)
Risk is a condition that cannot be identified accurately. Its existence is always referred to a situation that can cause negative effect such as destruction or loss. In construction works, the existence of risk is always linked to project delay or cost increase. However, this negative effect can be avoided or minimized. As a party who is responsible in running the construction works, contractors should be prepared to manage construction risk as to ensure the success of the project.